Sustainable Energy from Waste: A Feasibility Study in Miri, Malaysia - Chua, Ming Xuan; Hashim, Nur Hasyimah; Downmore, Musademba; Gani, Paran (Tecno Scientifica Publishing, 2023)
The growth of urban populations, industrialization, and economic development has led to a surge in solid waste production. When local recycling infrastructure falls short, much of this waste ends up in landfills, causing environmental and social challenges. This study aims to assess the feasibility of converting municipal solid waste (MSW) into energy, with a focus on combustion chamber modeling in Miri, Sarawak. Data on MSW composition are obtained from secondary sources. Ansys Fluent software is used to model the combustion chamber, and simulations are conducted to explore temperature, turbulence, and species distribution. MSW composition illustrates higher substantial fractions, with 39.8% being food waste, followed by 20.7% plastic/rubber. Calorific values range from 4652 kJ/kg for food waste to 32564 kJ/kg for plastic/rubber. Combustion simulations result in maximum flue gas temperatures of 1500 °C, 1200 °C, and 1800 °C under varying air inlet conditions. Turbulence intensities on the grate range from 125% to 174% for these air inlet configurations. The study concludes that moisture content significantly affects calorific value and heat generation during combustion. Higher turbulence intensities lead to increased reaction rates and heat generation, improving the energy efficiency of the process.